2019
DOI: 10.1002/ajhb.23355
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of low birth weight in India: An investigation from the National Family Health Survey

Abstract: Objective: This study aimed to estimate the change in prevalence of low birth weight (LBW) over the last decade in India and to identify its associated factors-biological, demographic, socio-economic, and programmatic. Methods:We used the data from the National Family Health Survey of 2005-2006 (NFHS-3) and 2015 -2016. The sample of this study included 11 300 children from NFHS-3 and 99 894 from NFHS-4 data; all these children were the last full-term singleton live-births, born within the last 3 years prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
55
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 32 publications
10
55
2
2
Order By: Relevance
“…This result is in accordance with the findings from Ghana where mothers who consumed diversified and nutritious foods were less likely to have LBW babies [19]. Similarly, an Indian study reported that the intake of high protein foods by mothers (i.e., consumption of dairy products) significantly reduces the risk of LBW [10]. Proper nutritious foods are essential for a healthy pregnancy as a healthy diet during pregnancy stimulates the baby's growth and development.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This result is in accordance with the findings from Ghana where mothers who consumed diversified and nutritious foods were less likely to have LBW babies [19]. Similarly, an Indian study reported that the intake of high protein foods by mothers (i.e., consumption of dairy products) significantly reduces the risk of LBW [10]. Proper nutritious foods are essential for a healthy pregnancy as a healthy diet during pregnancy stimulates the baby's growth and development.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, our study revealed that underweight women were at a greater risk of LBW babies. This finding is corroborated with many earlier studies conducted in India and elsewhere [8,10,11]. Nevertheless, the magnitude of risk may vary depending on the healthcare management and monitoring system in different geographical settings [8].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…e role of education and employment on infant birth weight might be due to various interactions among social determinants of health. Mothers with low educational attainment are prone to low health seeking behavior and more likely to be unemployed which further can lead to deprivation of nutritious food, good housing condition, and wealth which are found to be independent risk factors of LBW [19,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%